Periurbanização da leishmaniose visceral e emergência da coinfecção HIV/leishimania, no Rio Grande do Norte - Nascimento, Eliana Lúcia Tomaz do (2009)
Visceral leishmaniasis (VL) has undergone changes in terms of clinical and epidemiological presentation worldwide. Urbanization has been described in different regions of Brazil and the world, as well as in the state of Rio Grande do Norte. These changes have impacted in the clinical outcome of Leishmania infection. A new clinical entity called co-infection of HIV/Leishmania has been described as a consequence of overlapping areas of occurrence of VL and HIV / AIDS in different countries including Brazil. The aim of this study was to define the process of periurbanization of the LV and describe a case series of co-infection HIV / Leishmania in Rio Grande do Norte. A new demographic pattern of VL was detected, with an increase in the number VL adult male subjects. Analysis of spatial distribution of VL in the state of Rio Grande do Norte showed that in the past 20 years VL tends to occur in larger cities and therefore the highest risk disease is greater in the eastern and western regions. The first region included Natal, the state capital, where the process of suburbanization began in 1990, and more recently the city of Mossoró, the second largest state, where periurbanization began in the last five years. In 1990, the emergence of co-infection HIV/Leishmania in the state was observed. Case-control study revealed that the new clinical entity affects adult males, who acquired HIV through sexual intercourse, 40% of those with a preivous history of leishmania infection Relapse and death from LV is increased in HIV positive compared with HIV-negative patients matched by sex and age. This pattern is similar to the observed in Europe, except of the route of transmission, where in Europe occured concomitantly, by parenteral route in drug users. Analysis of spatial distribution identified overlapping new areas of occurrence of HIV / AIDS and LV potentially signaling to increased risk of this new clinical entity as described above. Therefore, epidemiological surveillance for co-infection HIV / Leishmania should be adopted in all areas of risk of VL. At the same time, it is necessary to evaluate drug resistance currently used in the treatment of VL, as well as parenteral transmission of L infantum/ chagasi in areas where drug dependence is a risk factor for HIV acquisition